HUBUNGAN SELF COMPASSION DENGAN KEPATUHAN TERAPI INSULIN PADA PASIEN DIABETES MELITUS TIPE 2 DI RSD DR. SOEBANDI JEMBER - Sutawardana, Jon Hafan; Putri, Wildiah Nursyafiqoh; Widayati, Nur (STIKes Maharani Malang, 2020)
ABSTRACT Introduction: Insulin therapy is one of the treatments in type 2 diabetes mellitus. Patients undergoing insulin therapy often experience side effects such as hypoglycemia. As a result, the patient feels a trauma that makes the patient change the insulin dose, ignores insulin injection time and lack of confidence when giving insulin injections independently. This condition makes managing blood sugar levels more difficult to achieve. This study aimed to analyze the correlation between self-compassion and adherence to insulin therapy in patients with type 2 diabetes mellitus at RSD dr. Soebandi Jember. Method: This research applied a descriptive correlational design with a cross-sectional approach. A total of 84 respondents obtained using consecutive sampling. Data collection conducted administering a questionnaire of the Self Compassion Scale (SCS) and the Morisky Medication Adherence Scale (MMAS-8). Data analyzed using the spearman correlation test with a significance level of 0.05. Result and analysis: The result showed a significant positive correlation between self-compassion and adherence to insulin therapy (p value=0.001; r=0.694). Discussion: Patients in managing diabetes need adherence to treatment. The existence of adherence in patients begins with the patient's self-acceptance of the illness. Self-compassion in patients is present when patients can accept themselves and love themselves without looking at the problem they face. The higher self-compassion makes a better adherence to insulin therapy. This study indicates the importance of self-compassion in patients with type 2 diabetes mellitus to improve insulin therapy compliance to control the patient's blood sugar levels. Key Words: Type 2 Diabetes Mellitus, Self compassion, Adherence to insulin therapy